2017
DOI: 10.1111/jcmm.13137
|View full text |Cite
|
Sign up to set email alerts
|

Collagen type XV and the ‘osteogenic status’

Abstract: We have previously demonstrated that collagen type XV (ColXV) is a novel bone extracellular matrix (ECM) protein. It is well known that the complex mixture of multiple components present in ECM can help both to maintain stemness or to promote differentiation of stromal cells following change in qualitative characteristics or concentrations. We investigated the possible correlation between ColXV expression and mineral matrix deposition by human mesenchymal stromal cells (hMSCs) with different osteogenic potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 52 publications
1
24
0
1
Order By: Relevance
“…We recently demonstrated that a chondroitin sulphate modified glycoprotein, the ColXV [20,21] is a critical regulatory component of the osteogenic pathway and that its expression in hMSCs is a prerequisite to promote the subsequent deposition of mineral matrix [23]. For the first time we correlated the increase of HIF-1α expression after hypoxia preconditioning with the increase of ColXV.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…We recently demonstrated that a chondroitin sulphate modified glycoprotein, the ColXV [20,21] is a critical regulatory component of the osteogenic pathway and that its expression in hMSCs is a prerequisite to promote the subsequent deposition of mineral matrix [23]. For the first time we correlated the increase of HIF-1α expression after hypoxia preconditioning with the increase of ColXV.…”
Section: Discussionmentioning
confidence: 80%
“…In order to investigate if hypoxia preconditioning has beneficial effects in making cells more prone to osteo-differentiation, the expression of ColXV, previously identified as predictive marker for selecting hMSCs with high osteo-differentiation potential [23], has been assessed at different levels. As reported in Fig.…”
Section: Colxv Expression In Hypoxia-preconditioned Hmscsmentioning
confidence: 99%
See 3 more Smart Citations